CLINICAL AND IMMUNOLOGICAL ASPECTS OF T C ELL-BASED VACCINE THERAPY IN PATIENTS WITH PROGREDIENT MULTIPLE SCLEROSIS - G. Seledtsova; I. Ivanova; S. Mamaev; D. Seledtsov; N. Malkova; V. Seledtsov; V. I. Seledtsov (Медицинская иммунология)
Abstract. Thirty-nine patients with a progredient clinical form of chronic multiple sclerosis (MS) were subject to multiple immunization with autologous polyclonal T-cell vaccines. Two years after initiating the vaccine therapy, no evidence for disease progression was noted in 16 patients (41% of total). Neurological improvement was observed in five cases (13%) from the vaccine-treated group. Of 22 control MS patients who did not receive the immunotherapy, only 6 persons (27%) exhibited stabilization of their clinical state. Clinical improvement was not detectable among this group of MS patients. A group of twenty-six MS patients was treated with Rebif, without evidence of disease progression in eleven cases (42%), and distinct neurological improvement noted in one patient (4%) from this group. One year after starting the vaccine therapy, a rise in serum IL-10 was detected in vaccine-treated patients, whereas IL-17 and IL-18 serum levels remained within the initial ranges. A correlation between the serum levels of anti-myelin antibodies and appropriate anti-idiotypic antibodies was revealed in these patients. In general, the results obtained suggest polyclonal T-cell vaccination as a potentially effective treatment approach, both at early and more advanced stages of the disorder.